Parotid and Sublingual Salivary gland as an Indicator of Antioxidant Efficacy in Experimentally Induced Diabetic Rats - Ghada EL-Gusbi; Laila Hamad; Magdy Ayad; Mohamed Shredah; Abd EL-Hafez Soliman (Khalij-Libya Journal of Dental and Medical Research, 2024)
The parotid and sublingual glands were considered the most appropriate tissues to study the effects of diabetes mellitus among the major salivary glands. Globally, diabetes mellitus is a major healthcare concern. It affects bodily tissues and organs in a variety of pathological ways, particularly the major salivary glands. Thirty adult, healthy albino rats were divided into three equal groups of ten animals each. Group I was a control group that did not receive any treatment, group II was experimentally induced to have diabetes mellitus using alloxan, a chemical agent that is more or less safe and permanent, and group III was experimentally induced to have diabetes but treated with ascorbic acid (Vit. C), as an antioxidant drug. All rat groups were sacrificed and tissue samples from their parotid and sublingual glands were prepared. The tissue samples studded histologically using Haematoxylin and Eosin (H&E) stain, histopathologically using Periodic acid Schiff's (PAS) reaction to detect carbohydrates, and immunohistochemically using Beta cell lymphoma-2 (BCL2) as an anti-apoptotic marker. Based on the histology, histopathological, and immunohistochemical significant lesions, the obtained results showed common alterations in the parotid and sublingual glands tissues of diabetic rats. However, compared to untreated animals, rats treated with the antioxidant vitamin C showed fewer tissue changes and lesions. According to the study's findings, vitamin C functions as a helpful antioxidant to assist avoid complications from diabetes. تم اعتبار الغدد النكفية وتحت اللسان من أكثر الأنسجة ملاءمة لدراسة تأثيرات مرض السكري بين الغدد اللعابية الرئيسية. على مستوى العالم، يعد مرض السكري من أهم المشاكل الصحية. فهو يؤثر على الأنسجة والأعضاء الجسدية بطرق مرضية متنوعة، وخاصة الغدد اللعابية الرئيسية. تم تقسيم ثلاثين فأرًا أبيض بالغًا سليمًا إلى ثلاث مجموعات متساوية تضم كل منها عشرة حيوانات. كانت المجموعة الأولى مجموعة تحكم لم تتلق أي علاج، والمجموعة الثانية تم تحريضها تجريبيًا على الإصابة بمرض السكري باستخدام الألوكسان، وهو عامل كيميائي آمن إلى حد ما ودائم، والمجموعة الثالثة تم تحريضها تجريبيًا على الإصابة بمرض السكري ولكن تم علاجها بحمض الأسكوربيك (فيتامين سي)، كدواء مضاد للأكسدة. تم التضحية بجميع مجموعات الفئران وتم تحضير عينات الأنسجة من الغدد النكفية وتحت اللسان. تم فحص عينات الأنسجة نسيجيًا باستخدام صبغة الهيماتوكسيلين والإيوسين (H&E)، ونسيجيًا باستخدام تفاعل شيف الدوري الحمضي (PAS) للكشف عن الكربوهيدرات، ومناعيًا كيميائيًا باستخدام ليمفوما الخلايا بيتا 2 (BCL2) كعلامة مضادة للموت الخلوي. بناءً على الآفات المهمة في علم الأنسجة والهيستولوجيا والهيستولوجيا والمناعية الكيميائية، أظهرت النتائج التي تم الحصول عليها تغيرات شائعة في أنسجة الغدة النكفية وتحت اللسان لدى الفئران المصابة بمرض السكري. ومع ذلك، بالمقارنة مع الحيوانات غير المعالجة، أظهرت الفئران المعالجة بمضاد الأكسدة فيتامين سي تغيرات وإصابات أقل في الأنسجة. وفقًا لنتائج الدراسة، يعمل فيتامين سي كمضاد للأكسدة للمساعدة في تجنب المضاعفات الناجمة عن مرض السكري